MISLABELING OF JUVENILE TENUALOSA SPP. AS GUDUSIA CHAPRA IN THE FISH MARKETS AND RIVERS OF BANGLADESH - Sanzida Afrin; Mahmuda Begum; Mehrab Chowdhury; Nahid Sultana; Shilpi Saha; Anirban Sarker; Mohammad A Baki (Jakarta Technical University of Fisheries, 2024)
Juveniles ilish, Tenualosa spp. Fowler, 1934 named Jhatka mislabeling is a documented problem that has significant effects on consumers’ demand, resource limitation, and complex supply chain. When jhatka is sold as chapila then its correct scientific/accepted name, jhatka fake permits unlawfully caught species entering the market. The result of fraudulent activity included consumers’ losses, illegal harvesting, and more ilish resource degradation. It is vital that these fraudulent activities should be defined. This paper examines the mislabeling of ilish at different stages such as harvesting, market, and consumers level. Both morphomeristic and molecular analyses were used to identify the fishes. The samples were collected from different types of markets and rivers. Mislabeling at different stages of the supply chain including illegal harvesting of jhatka has been identified. Circulating mislabeling records could also encourage law-enforcement agencies, fishermen, sellers, and consumers to more closely assess.